The adult worker model family, gender equality and care : the search for new policy principles, and the possibilities and problems of a capabilities approach - Giullari, Susanna; Lewis, Jane.; United Nations Research Institute for Social Development (Geneva : United Nations Research Institute for Social Development, 2005)
Summary. - Résumé. - Resumen.
Keywords: perheet; työ; hoivatyö; sukupuoli; tasa-arvo.